2020
DOI: 10.1128/cmr.00151-19
|View full text |Cite
|
Sign up to set email alerts
|

Mumps: an Update on Outbreaks, Vaccine Efficacy, and Genomic Diversity

Abstract: SUMMARY Mumps is an acute viral infection characterized by inflammation of the parotid and other salivary glands. Persons with mumps are infectious from 2 days before through 5 days after parotitis onset, and transmission is through respiratory droplets. Despite the success of mumps vaccination programs in the United States and parts of Europe, a recent increase in outbreaks of mumps virus infections among fully vaccinated populations has been reported. Although the effectiveness of the mumps virus component o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 159 publications
(236 reference statements)
2
32
0
2
Order By: Relevance
“…Several reviews, both observational and systematic have demonstrated the clinical benefit of a mumps vaccine ( 107 , 108 ), the pathogenesis and genomic diversity of the MuV ( 10 , 107 , 108 ) and the epidemiology surrounding the outbreak ( 1 , 10 , 82 ). It is not clear why these mumps outbreaks occur, although it has been alluded to be due to a number of interrelated factors, such as sub-optimal vaccine uptake ( 1 , 109 , 110 ), primary or secondary vaccine failure or failure of the mumps vaccine to protect individuals from infection (vaccine efficacy) ( 107 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews, both observational and systematic have demonstrated the clinical benefit of a mumps vaccine ( 107 , 108 ), the pathogenesis and genomic diversity of the MuV ( 10 , 107 , 108 ) and the epidemiology surrounding the outbreak ( 1 , 10 , 82 ). It is not clear why these mumps outbreaks occur, although it has been alluded to be due to a number of interrelated factors, such as sub-optimal vaccine uptake ( 1 , 109 , 110 ), primary or secondary vaccine failure or failure of the mumps vaccine to protect individuals from infection (vaccine efficacy) ( 107 ) ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common clinical features include fever, bilateral parotid gland swelling, headache, nausea, vomiting, and sometimes seizures. The neurological complications linked with mumps include sudden-onset sensorineural hearing loss, aseptic meningitis, which is usually benign and encephalitis, which is associated with grave consequences, including death [6]. Ocular involvement may lead to follicular conjunctivitis, episcleritis, dacryoadenitis, keratitis, scleritis, anterior uveitis, choroiditis, and paralysis of extraocular muscles (abducens nerve palsy), although rare, there can also be bilateral optic neuritis after an encounter with mumps virus [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ocular involvement may lead to follicular conjunctivitis, episcleritis, dacryoadenitis, keratitis, scleritis, anterior uveitis, choroiditis, and paralysis of extraocular muscles (abducens nerve palsy), although rare, there can also be bilateral optic neuritis after an encounter with mumps virus [7]. Mumps is preventable with the administration of the measles-mumps-rubella (MMR) vaccine, with effectiveness after a single dose ranging from 49-92% (median: 78%), and to 66-95% (median:88%), after administration of the second dose [6].…”
Section: Discussionmentioning
confidence: 99%
“…A booster dose of the mumps vaccination is currently recommended only in the setting of an outbreak [9,10,[26][27][28]. Although the level of protective antibodies and correlates of protection against mumps infection are not well-defined, suggested causes of the resurgence of infections have included waning immunity over time due to a lack of a durable T-cell mediated response, as well as antigenic differences between vaccine and circulating mumps strains, [1,4,[7][8][9][10][26][27][28][29][30][31]. As such, the mismatch between vaccine and circulating mumps strains has also prompted the consideration of a polyvalent vaccine [1,32].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, missing data could not be accounted for and information on risk factors was not available since the secondary data that was analysed did not include information about clinical and medical history. Secondly, 50% of mumps infections present non-specifically or with respiratory symptoms, while 20-40% of infections are reportedly asymptomatic or have mild symptoms [1,27,40]. These cases may not present at health facilities and would therefore not have been accounted for in the data that we reviewed.…”
Section: Discussionmentioning
confidence: 99%